1973
DOI: 10.1677/joe.0.0560361
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Metabolism of Labelled Corticosteroids in the Duck (Anas Platyrhynchos)

Abstract: After the injection of [1,2-3H]corticosterone into ducks, no unaltered free [1,2-3H]corticosterone was found in either bile, gut contents or cloacal fluid. All the [1,2-3H]corticosterone metabolites in cloacal fluid had similar chromatographic mobilities. A portion of these metabolites was steroid ester sulphate but enzymic hydrolysis suggested that only a small fraction of the sulphate was conjugated to [1,2-3H]corticosterone. The amount of ester sulphate in samples of cloacal fluid, however, was highly varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The present report reveals a recovery of 75% of each radiolabeled steroid administered within 24 hr after radiolabel injection. This high recovery supports the concept that circulating steroids are rapidly cleared and therefore recovered more efficiently in some avian species [Helton and Holmes, 1973;Holmes et al, 1974;Holmes and Slikker, 1976], compared to mammals.…”
Section: Discussionsupporting
confidence: 78%
“…The present report reveals a recovery of 75% of each radiolabeled steroid administered within 24 hr after radiolabel injection. This high recovery supports the concept that circulating steroids are rapidly cleared and therefore recovered more efficiently in some avian species [Helton and Holmes, 1973;Holmes et al, 1974;Holmes and Slikker, 1976], compared to mammals.…”
Section: Discussionsupporting
confidence: 78%
“…For BM, Helton and Holmes (1973; mallard Anas platyrhynchos) as well as Krawany (1996; domestic goose) concluded that the hepato-renal pathway may even be more important than the hepatointestinal one. For BM, Helton and Holmes (1973; mallard Anas platyrhynchos) as well as Krawany (1996; domestic goose) concluded that the hepato-renal pathway may even be more important than the hepatointestinal one.…”
Section: Discussionmentioning
confidence: 99%
“…Since the half-life (r^) of corticosterone in the duck is normally about 10 min (Bayle, Boissin, Daniel & Assenmacher, 1971;Helton & Holmes, 1973;Holmes, Broock & Devlin, 1974;Holmes & Kelly, 1976) and is even less in stressed birds ), the high levels of corticosterone maintained after stress or ACTH administration may have resulted from a greater release of the hormone from the adrenal cortex throughout these periods. However, the inability of exogenous, heterologous ACTH (which would probably have a ti of less than 10 min) to have any greater effect than saline during the first 20 min after its administration demonstrated that the release of corticosterone during this time must be maximal and that peak levels of corticosterone of 30-40 ng/ml plasma resulted only from ACTH-induced corticosteroidogenesis.…”
Section: Discussionmentioning
confidence: 99%